Selecting an alternative to solve a problem from several available alternatives. Issue 1 (January 2021) - Dodun, O; Slătineanu, L; Arcidiacono, G; Coteaţă, M; Nagîţ, G; Hriţuc, A
Abstract: When for a certain design problem many alternative solutions could be susceptible to be used, a selection activity should be developed. If in the case of simple problems, the identification of an applicable alternative could be made very fast, in the case of the complex problems, the identification of the most convenient alternative could constitute itself a difficult problem. Over the years, simpler or more complex methods were found and applied to help the problem solver in finding the most convenient applicable alternative. The selection of a certain alternative when many such alternatives seem to exist could be made using the double input matrix method and the method of the pairwise comparison matrix and distinct evaluation criteria. The results of a applying the two selection methods in the case of necessity to establish a machining scheme for an electrical discharge machining process were presented in the paper.